2020
DOI: 10.1038/s41392-020-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profiling of plasma cytokines, chemokines and growth factors from mild, severe and fatal COVID-19 patients

Abstract: , a novel coronavirus that is related to severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) in phylogenetic distance was identified. 1 This virus, which was later designated as SARS-CoV-2, also causes acute respiratory disease syndrome (ARDS) termed coronavirus disease 2019 (COVID-19), which was declared as a pandemic by the World Health Organization in March 2020. Although the majority of patients of COVID-19 show moderate symptoms such as dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
130
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(145 citation statements)
references
References 6 publications
13
130
2
Order By: Relevance
“…The MAPK, which plays a critical role in the release of various cytokines, including IL-1, IL-10, IL-12, and TNFα, is also modulated by Ang II [66]. Several clinical studies have indicated a marked increase of proinflammatory cytokines, like IL-2, IL-6, and TNF-α, in severe and moderate cases of COVID-19 [67][68][69][70][71][72][73].…”
Section: Ace2 and Cytokine Storm The Main Mechanism Of Covid-19 Compmentioning
confidence: 99%
“…The MAPK, which plays a critical role in the release of various cytokines, including IL-1, IL-10, IL-12, and TNFα, is also modulated by Ang II [66]. Several clinical studies have indicated a marked increase of proinflammatory cytokines, like IL-2, IL-6, and TNF-α, in severe and moderate cases of COVID-19 [67][68][69][70][71][72][73].…”
Section: Ace2 and Cytokine Storm The Main Mechanism Of Covid-19 Compmentioning
confidence: 99%
“…Recent clinical studies have found that COVID-19 patients with severe illness had elevated levels of certain cytokines including IL-6, TNF-α, IL-10, MCP-1 and IP-10 [6][7][8]. The pathophysiology of COVID-19 is far from being understood, and the absence of an effective medical regimen has led to the development of new therapeutic strategies based on pathophysiological assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a person with FXS may have impaired immunity and may be more susceptible to infectious diseases. CXCL-10 has also been implicated in the cytokine storm linked to a more severe disease among patients with COVID-19 [ 6 , 8 , 9 ]. Consequently, one hypothesis could be that patients with FXS infected with COVID-19 should display a lesser degree of inflammation and milder disease.…”
Section: Discussionmentioning
confidence: 99%